"If you've done a good job, it's as if you've never existed": Translators on translation in development projects in the Sahel. Issue 1 (2nd January 2021) - Heywood, Emma; Harding, Sue-Ann
ABSTRACT: Translation is an essential and extensively-used tool in research and development projects, yet is frequently sidelined as an insignificant or minor component in the initial design. This often leads to assumptions regarding translation tasks, by both the translator and the end-user or the commissioner. Addressing this lack of awareness and the resultant misunderstandings concerning the translation outcome, this article examines translation processes that take place when translations are commissioned. It draws on empirical data from an NGO radio development project in Africa's Sahel, including semi-structured interviews with translators working from Fulfuldé, Tamashek, and Zarma-Songhai into French with responses clustered around four themes: identity, agency, source text knowledge and transcription/translation processes. Contributing to translation studies and to development studies, the article provides recommendations on implementing changes to overcome dismissive attitudes towards translation, and to promote its consideration as a core element of development and research projects.